Developing Students’ Learning Interests in Islamic Religious Education through Contextual Teaching and Learning Method - Suhadak, Dawud; Inayati, Nurul Latifatul (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Education is an inherent component of human life and existence, both formal and informal learning. Because it is conceivable to claim that education is an essential component of human existence. This research is important because it can provide insight into how the Contextual Teaching and Learning (CTL) method can increase students’ interest in learning Islamic Religious Education (Pendidikan Agama Islam/PAI). This research aims to examine how the implementation of the Contextual Teaching and Learning approach at SMP Negeri 1 Kedawung can increase students’ interest in learning PAI. This research uses a qualitative approach with descriptive methodology to describe the effectiveness of CTL techniques in increasing students’ interest in learning. Data was collected through interviews, observations and document analysis involving PAI teachers and students as research subjects. The research results showed that the application of the CTL method can significantly increase students’ interest in learning. This happens through the relationship of teaching materials with real experiences, the use of varied learning media, and the active involvement of students in the learning process. Students were more motivated to understand Islamic religious values ​​because this method creates relevant, meaningful and interesting learning. Teachers play an important role as facilitators by integrating Islamic values ​​in learning activities, so that students not only understand theory, but can also apply it in everyday life. In conclusion, students’ learning interest can be increased effectively through the implementation of CTL method.